MELAKA dan Arus Gerakan Kebangsaan Malaysia - Abdul Latiff Abu Bakar (Institut Kajian Sejarah dan Patriotisme Malaysia Penerbit Universiti Malaya, 1996)
History of the role of Malaka in Malaysia's national movements; papers of a conference.